Profil pengembangan social learning dimensi imitasi pada ekstrakurikuler karawitan sekolah dasar - Wardani, Khusnul Mutiara; Karsono, Karsono (Universitas Sebelas Maret, 2026)
This study aims to describe the development of imitation dimensions in karawitan learning in extracurricular activities at SDN Sumber 6 No.255 Surakarta based on a social learning perspective. This study uses a qualitative method with observation, interview, and documentation techniques. The results of the study indicate that the four aspects of the imitation dimension have developed well, namely imitation of physical movements, sound patterns and rhythms, social and collective actions, and expressions in gamelan playing. The imitation process is seen in the way students imitate playing techniques from coaches and peers, adjust the tempo in groups, and apply habits and ethics of playing gamelan. This imitation-based learning not only helps students master musical skills, but also forms cooperation, discipline, and respect for culture. The implications of this study confirm that gamelan learning can be an effective medium in developing social skills through the process of observation and interaction in groups.